PERANCANGAN INTERIOR TOKO OLEH-OLEH DAN KAFETARIA BRAWIJAYA UNTUK MEMPERKUAT BRAND PERUSAHAAN - Valentina, Ivana; Kusumowidagdo, Astrid; Wardhani, Dyah Kusuma (Universitas Ciputra Surabaya, 2020)
One of Indonesian’s cultures is bring back souvenirs for their friends and relatives when they travel. Souvenirs usually present a specialty of a certain place. Brawijaya Istana Oleh-Oleh is a souvenir shop in Batu which sells souvenirs, such as snacks, clothes, and accessories. Brawijaya’s facilities are cafeteria, Islamic prayer room (musholla), hostel, rest area, parking space, and bathrooms with hot water. Cafeteria and clothes retail store are the areas that will be designed. Cafeteria in Brawijaya is leased for group of tourists. It doesn’t sell foods, the foods are provide by outsource local caterings. The featured products of clothes retail store are batik fabric and t-shirt that produced by local small and medium retailers. Brawijaya’s visions are to becomethe most complete and affordablesouvenir shop in Batu and also make cooperation with local small and medium retailers and artists. The design has to pay attention of circulation path and room organization to ease consumers finding products. Design of Brawijaya’s cafeteria and clothes retail store using “Connecthings” as the concept, which means, “connect things” connecting Brawijaya’s vision and consumer’s need into layout arrangement and interior design. The application concepts are by locating featured products, which produced by local and medium retailers, in the most strategic place. Graphics on the wall is designed by local artist, to support Braiwjaya’s vision. Products displays in retail store are arranged based on Market Segments Grouping, in order to ease the tourists with the short shopping time finding their needs. Logo application is visually and philosophically implemented in the interior elements to strengthen Brawijaya’s branding.